Estudo da vasorreatividade cerebral em crianças com doença falciforme: avaliação pelo doppler transcraniano - Campos, Rejane de Souza Macêdo [UNIFESP] (2016)
Objectives: The purposes of this study were: to evaluate cerebral blood flow velocities and vasoreactivity using transcranial Doppler (TCD) in children with SCD and to compare them with healthy subjects; to compare cerebral blood flow velocities and vasoreactivity with TCD in children with SCD, with and without migraine, and healthy subjects; to determine headache and migraine frequencies in children with SCD. Methods: Children aged 10 to 18 years old with SCD were evaluated from the hemoglobinopathy clinics at UNIFESP. Healthy children of similar age and gender were included. A structured questionnaire was applied to all patients evaluating the presence of headache, its frequency and if migraine criteria were fulfilled. Demographic characteristics, comorbidities, medication use, laboratory and imaging exams data were collected from medical records. TCD was performed in all patients and controls subjects, with breath-holding maneuver and calculation of the breathholding index (BHI) to assess cerebral vasoreactivity. Cerebral blood flow velocities were assessed in both middle, anterior, posterior, vertebrals and basilar arteries. Cerebral blood flow velocities and vasorreactivity were compared between patients and control subjects and also between patients with SCD with and without migraine and healthy controls. Statistical analyses were performed using SPSS 18.0. Results: TCD was performed in 42 patients, mean age 12,67?2,18 years, and 20 controls subjects, mean age 13,90?3,04 years. Blood flow velocities were higher in patients with SCD than health volunteers in all arteries evaluated. Cerebral blood flow velocities were negatively correlated with hemoglobin levels (p<0,05). BHI was abnormal in 19% of the patients and in none of the controls (p=0.04). BHI values in patients were significantly lower than in control subjects (p<0.01 at right and p=0.01 at left). There were no differences in blood flow velocities between patients with or without migraine. BHI was similar in children with SCD with or without migraine, and between both and control subjects. A total of 57,1% had headache and 38% fulfilled criteria for migraine Conclusions: Cerebral vasoreactivity may be impaired in children with SCD, with BHI significantly lower in this group, maybe reflecting a low vascular reserve and autoregulation capacity in these patients. Cerebral vasoreactivity was not different between patients with or without migraine and both and controls subjects. Migraine was found in more than one third of our patients.